Degradation of organic compounds in a fenton system based on chitosan/Fe-0/Fe2O3 composites: a theoretical and experimental study - Ferreira, Lais O.; Lemos, Ana C. C.; Nogueira, Francisco G. E.; Guimaraes, Iara R.; Guerreiro, Mario C.; Rocha, Marcus V. J.; Savedra, Ranylson M. L.; Hammer, Peter [UNESP]; Brito, Angela D. B.; Cunha, Elaine F. F. da; Silva, Joaquim P.; Ramalho, Teodorico C. (Springer, 2016)
Chitosan is a polymer with interesting characteristics for use in catalysis, such as biocompatibility, high chemical reactivity and stability under various conditions. Seeking new applications, a new hybrid material was synthesized for use in the degradation of organic compound. A synthesis route proposed led to the formation of a material in the form of film. The characterization data indicated the presence of hematite, as well as metallic iron. In addition, a theoretical model for interaction of iron with chitosan was proposed. Molecular dynamics simulations indicate that non-Coulomb interactions modulate the adsorption process between reactive red dye and chitosan. The catalytic behavior of these hybrid materials was investigated for the H2O2 decomposition to O-2 and the degradation of reactive red dye. The hybrid material showed high degradation capacity, confirming this material as an efficient heterogeneous Fenton catalysts.
Keywords: Chitosan; Fenton process; Iron; Dye